2022
DOI: 10.1002/csr.2438
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing and comparing the different effects between internal and external corporate social responsibility perceptions and organizational citizenship behavior: A need theory perspective

Abstract: This study examines the comparative effects of internal and external CSR perceptions on organizational citizenship behavior (OCB) and focuses on two consequences to compare CSR perception types. It also attempts to develop logical linkages between CSR perceptions and OCB through individual-level psychological mechanisms, perceived external prestige, and affective commitment. The study is centered around the Chinese manufacturing and service industries using an online data-collection platform similar to Qualtri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…Thus, employees' perceptions of organizational support will. Second, internal CSR activities are aimed at improving employee well-being (Farooq et al, 2017;Wang et al, 2022), in turn promoting employees to perceive more support from their organization (Chen et al, 2023). Thus, there is a positive relationship between perceived internal CSR and perceived organizational support.…”
Section: 4mentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, employees' perceptions of organizational support will. Second, internal CSR activities are aimed at improving employee well-being (Farooq et al, 2017;Wang et al, 2022), in turn promoting employees to perceive more support from their organization (Chen et al, 2023). Thus, there is a positive relationship between perceived internal CSR and perceived organizational support.…”
Section: 4mentioning
confidence: 99%
“…, 2017; Wang et al. , 2022), in turn promoting employees to perceive more support from their organization (Chen et al. , 2023).…”
Section: Theory and Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, empirical evidence of how the external publics perceive these two types of statements is still lacking. Moreover, research has suggested that there are different mechanisms underlying people's perceptions of corporate CSR communication on external versus internal actions, which can lead to differential outcomes of these two types of corporate statements (Aggarwal and Singh, 2023; Chen et al , 2022; Hameed et al , 2016).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%